INTEGRASI NILAI ISLAM DALAM MANAJEMEN PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Sri Hidayati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Islamic Religious Education (PAI) management faces complex challenges in the era of globalization and digital transformation, particularly in maintaining a balance between learning innovation and the internalization of Islamic values. The primary issue lies in the suboptimal integration of Islamic values within managerial functions in a systematic and holistic manner. This study aims to examine the implementation of Islamic values in PAI management and its impact on improving educational quality and shaping students’ character. The research employs a qualitative method using a literature review approach, drawing on nationally and internationally indexed scientific journals published between 2016 and 2026. Data analysis was conducted thematically using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the internalization of Qur’anic values such as hikmah (wisdom), ‘adl (justice), amanah (trustworthiness), and ihsan (excellence) within managerial functions can foster an organizational culture that is fair, participatory, and spiritually oriented. Furthermore, PAI management plays a significant role in strengthening religious moderation, supporting value-based technological adaptation, and promoting Islamic leadership grounded in nawaitu (sincere intention). This study concludes that value-based Islamic PAI management is an effective strategy for enhancing educational quality while fostering students’ noble character.